Implementation Of Regulation Number 02 Of 2011 Concerning Waste Management In Bengkulu City - Fernando, Yuri; Aminudin, Achmad; Farozi Agus, Nour (Green Publisher Indonesia, 2024)
Other waste management issues stem from the lack of a professional waste management system planning. The waste management sector has not yet received priority compared to other sectors in urban development. This research utilizes a qualitative approach. In this study, to determine the implementation of the Bengkulu City Regional Regulation Number 02 of 2011 Regarding Waste Management in Bengkulu City based on the opinions expressed by Nugroho and the modified results between the Bengkulu City Regional Regulation Number 02 of 2011 Regarding Waste Management. Regarding the policy socialization aspect, it is noted that the socialization of regional regulations to the community is still uneven. Furthermore, for the socialization related to waste separation, similar responses were received. This is proven by organic waste still being seen in inorganic waste bins. In terms of planning, the provision of waste bins in public and social facilities is still unavailable in some facilities. Furthermore, regarding waste management financing, there are various tariff rates. For waste management conducted by LPM or third parties, the tariff is determined through mutual agreement. Meanwhile, waste management by the Department will be subject to agreed-upon fees. In terms of implementation, for supervision and oversight, researchers can conclude that the people of Bengkulu City feel the supervision being carried out. In terms of evaluation, the application of sanctions and criminal provisions received various responses. Some members of the community disagree with the rules, while others agree, in order to instill a deterrent effect and raise awareness to dispose of waste properly. Furthermore, waste management by LPM and the Department can be concluded to still not be fully operational, as evidenced by increasing piles of waste before the transportation process.